"Bisphenol a: an emerging threat to male fertility" - Federica Cariati; Nadja D'Uonno; Francesca Borrillo; Stefania Iervolino; Giacomo Galdiero; Rossella Tomaiuolo (BMC, 2019)
Abstract Background Among the factors causing male infertility, one of the most debated is the exposure to environmental contaminants. Recently, the chemical compound Bisphenol A (BPA) has drawn attention from the reproductive science community, due to its ubiquitous presence in day-to-day life. Its toxic action appears to mainly affect the male reproductive system, directly impacting male fertility. Main The purpose of this review is to investigate current research data on BPA, providing an overview of the findings obtained from studies in animal and human models, as well as on its supposed mechanisms of action. Conclusion A clear understanding of BPA action mechanisms, as well as the presumed risks deriving from its exposure, is becoming crucial to preserve male fertility. The development and validation of methodologies to detect BPA toxic effects on reproductive organs can provide greater awareness of the potential threat that this chemical represents.